Could stocks hedge against inflation in the MENA region? - El Adly, Laila (AUC Knowledge Fountain, 2017)
The dissertation examines the effect of unexpected inflation on stock returns in the MENA region (Egypt, Jordan, Kuwait, Morocco, Qatar, United Arab Emirates (UAE), Tunisia, and Saudi Arabia). Our sample covers the MENA region over the period 2005 – 2016. We examine the long run relation between unexpected inflation and stock returns using the Vector Error Correction Model (VECM) and we model for the unexpected inflation using Autoregressive Moving Average (ARMA). Also, we capture the joint volatility dynamics between unexpected inflation and stock returns using the multivariate VECH-GARCH. The results reveal that there are variations depending on the country examined. Using Johansen (1995) trace test for co-integration, our results affirm the existence of long run relation between stock returns and unexpected inflation in Egypt and Jordan. As for the other countries, there are short-term dynamic linkages between the two variables in Kuwait, Morocco, Qatar, UAE, and Saudi Arabia. For modelling the volatility of unexpected inflation and stock returns, we use the VECH-GARCH. The volatility results suggest that the news effect has a significant and positive impact on stock returns in Jordan, Kuwait, Qatar, Dubai, and Saudi Arabia. On the other hand, the memory effect of the volatility in stock returns is significant for all countries except Tunisia and Egypt.